2007
DOI: 10.1016/j.biopsych.2007.02.015
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1A Receptor Binding in Temporal Lobe Epilepsy Patients With and Without Major Depression

Abstract: Background-Major depressive disorder (MDD) is the most common comorbid psychiatric condition associated with temporal lobe epilepsy (TLE). Preclinical and clinical studies suggest that 5-HT 1A receptors play a role in the pathophysiology of both TLE and MDD. There is preliminary evidence for an association between decreased 5-HT 1A receptor binding in limbic brain areas and affective symptoms in TLE patients. The objective of this study was to compare 5-HT 1A receptor binding between TLE patients with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(64 citation statements)
references
References 50 publications
(62 reference statements)
5
53
0
5
Order By: Relevance
“…In particular, Gilliam et al (54) reported greater resting temporal lobe hypometabolism in patients who reported higher levels of depression, and Victoroff et al (60) found an association between the severity of left temporal lobe hypometabolism and the frequency of major depressive episodes in patients with epilepsy. There is also recent evidence demonstrating an association between reduced 5-HT(1A) receptor binding in the hippocampus and higher levels of self-reported depression in patients with TLE (61,62). In another study, a trend was noted for increased left amygdalar, but not hippocampal, metabolism to correlate with increased depression in TLE (21).…”
Section: Petmentioning
confidence: 94%
“…In particular, Gilliam et al (54) reported greater resting temporal lobe hypometabolism in patients who reported higher levels of depression, and Victoroff et al (60) found an association between the severity of left temporal lobe hypometabolism and the frequency of major depressive episodes in patients with epilepsy. There is also recent evidence demonstrating an association between reduced 5-HT(1A) receptor binding in the hippocampus and higher levels of self-reported depression in patients with TLE (61,62). In another study, a trend was noted for increased left amygdalar, but not hippocampal, metabolism to correlate with increased depression in TLE (21).…”
Section: Petmentioning
confidence: 94%
“…32,33 The ROI was an ellipsoid that fit well within the anterior hippocampus and spanned five 2-mm axial slices. For each subject, the ROI in each slice was repositioned such that only hippocampus was included within the ROI.…”
Section: Mri Acquisition and Preprocessingmentioning
confidence: 99%
“…These studies revealed similar functional abnormalities in primary MDD and temporal lobe epilepsy (TLE) (without depression), which consisted of decreased 5-HT1A receptor binding in the hippocampus, amygdala, cingulate gyrus, insula, and raphe nucleus [13][14][15][16]. In one study of patients with TLE and normal hippocampus volume, the decrease in 5-HT 1A binding was restricted to the temporal pole [17], and was more pronounced in the seizure-onset zone and in regions where the discharge propagated than in regions where only interictal paroxysms or no epileptic activity was recorded [18].…”
Section: Serotoninmentioning
confidence: 82%